Comparison of geometrical, momentum and mass transfer characteristics of real foams to Kelvin cell lattices for catalyst applications. (May 2017) - Lucci, Francesco; Della Torre, Augusto; Montenegro, Gianluca; Kaufmann, Rolf; Dimopoulos Eggenschwiler, Panayotis
Highlights: Micro-CTs of real ceramic and metallic foams for exact determination of foam structural properties. Micro-CTs of real foams for deriving equivalent Kelvin cell lattices. CFD analysis of momentum and mass transfer through CT's of real foams and their Kelvin cell equivalent. The trade off between Mass transfer and pressure drop is generally 10–15% higher in Kelvin cell structures compare to real foams. Abstract: Open cell foams are considered promising catalytic substrates providing high surface area and a tortuous structure resulting in enhanced mass transfer characteristics. CFD analysis, recently, has focused in pointing structures with favourable reactivity-flow resistance characteristics. In order to reduce the geometrical complexity and computational efforts, foams have been modelled as regular (polyhedric) open cell structures. In this study a comprehensive comparison of real foams with equivalent Kelvin cell lattices is performed in CFD. Therefore 4 typical foams (two ceramic and two metallic) have been chosen. Geometric properties have been accessed with Micro-Tomography scans. Randomised Kelvin cell lattices have been generated matching porosity and specific surface area of the scanned real foams. Geometric, momentum and mass transfer characteristics of real foams and Kelvin cell lattices are analysed with CFD. Kelvin cell lattices showed similar behaviour in respect to their real foam equivalents, had though clearly better reactivity-pressure drop trade-offs. Based on the results presented best performances as a catalyst can be expected by 3D printed, additive manufactured, high porosity polyhedric structures.